ANALYSIS OF PERFORMANCE APPRAISAL OF FARMER GROUPS (Case Study of Farmers' Groups in Cinta Damai Village Unit Cooperative (KUD), Tapung Hilir, Kampar) - Wulan Ayu Ningsih; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at the Village Unit Cooperative (KUD) located in Cinta Damai Village, Tapung Hilir District, Kampar Regency. The purpose of this study was to analyze the performance and performance evaluation of farmer groups in the Cinta Damai Village Unit Cooperative (KUD), Tapung Hilir, Kampar. In this research the method used is descriptive qualitative. The sampling technique used in this study is snowball sampling. Data collection techniques through observation, interviews and literature study. Types and sources of data use primary data and secondary data. The results of this study are the results of the work (performance) of farmer groups based on an assessment that has been able to be said to be good or has been satisfactory for the KUD. The KUD does not judge by ranking, but through the process of taking a number of farmer groups that do work in accordance with the work standards that have been set based on the conclusions reported by the assessors to KUD for a certain period of time. Based on the analysis that has been done, the process of evaluating the performance of farmer groups in KUD has been done quite well. The assessor does not miss anything that becomes the evaluation criteria, in this case in accordance with what is in the field. Keywords: Performance, Performance Assessment